Selective interactions between epithelial tumour cells and bone marrow mesenchymal stem cells - Hombauer, H (Nature Publishing Group, 2000)
This work is a comparative study on the features displayed by an epithelial metastatic breast cancer cell line (MCF-7) when set in co-culture with human bone marrow mesenchymal stem cells (MSC) or a feeder layer of 3T3 fibroblasts. MSC, a subset of non-haematopoietic cells in the marrow stroma, display a potential for self-renewal, proliferation and differentiation into precursors for bone, cartilage, connective and muscular tissue. Adhesion of MCF-7 cells to monolayers of MSC or 3T3 was high (95 and 85% respectively). Once attached, MCF-7 grow well on both monolayers. Morphology of MCF-7 cells, as analysed by light and epifluorescence microscopy, revealed that MCF-7 cells grow in clusters on 3T3, but disperse on MSC. Concomitant with the lost of their aggregation status, MCF-7 on MSC express low levels of the intercellular adhesion molecules, E-cadherin and epithelial-specific antigen (ESA). These results suggest that MSC represent an appropriate cell target to investigate the cellular and molecular events occurring at the interface of epithelial-marrow stromal interactions. Together, the model here described should permit to further evaluate the significance and prognostic impact of the shift of micrometastatic cells from a cluster-aggregated into a single-cell status. © 2000 Cancer Research Campaign